POTENTIALS OF BACILLUS STEAROTHERMOPHILLUS FOR ENHANCED OIL RECOVERY A LABORATORY EXPERIMENT - M. Udiharto; S. Kadarwati; E. H. Legowo; M. Rahman; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1995)
B. stearothermophillus was isolated from among microbes recovered from a formation water from an oil field in Indonesia, where the temperature was 55Â°CLaboratory experiment was conducted to measure the growth, and to study the effects of its activity on the physical characteristics of reservoir rock and crude oil in an oil well.